(3fSNI SLd GdeLJHis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3ef YHO ehdGfG HGdMbjbI hEdg GdCRdjI GdhGMO GdUeO GdMGce GdefaQO Ld PcQg hYR CSeg hdG eYHhOkG ShGg heedhcI MeRg Hf Ydi Hf CMeO s
(3BNQgG (B:s
(3hCTcQ ehdGfG Ld PcQg Ydi eG ChdGc ef fYeI GdYXjeI hGdBjI GdSfjI djRjOc ef aVdg hjKHJc Ydi WGYJg Efg hdi Pdc hGdbGOQ Ydjg Je JbdO GdeLJHi hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds